Transmutation. - Tan, Siew Khim. (2012)
This paper explores by merging the concept of Chinese Alchemy into a game, this project aims to achieve more possible solutions and even inventive ways to play in the game. Using the different various spells in the game, the player had a choice to decide how to use it and when to use it. The players can use the spells to their advantage or even found themselves harmed by the spells. Hence, it is up to the player's choice in using the spells and various outcomes will be created based on the player's decision.